Analysis of Metaphorical Expressions Used in Adele’s Song Lyrics “Someone Like You” - Juliana Juliana; Santi Arafah; Fadhila Rahma Handayani; Fiore Arayu Hutagalung (Universitas Muhammadiyah Enrekang, 2023)
Metaphorical expressions play a crucial role in music, enabling artists to communicate complex emotions and experiences through vivid and imaginative language. This research examined the metaphorical expressions used in the lyrics of Adele's famous song